Intracardiac electrode detection of early ischaemia in man. Issue 3 (September 1983) - Donaldson, R M; Taggart, P; Swanton, H; Fox, K; Noble, D; Rickards, A F
Abstract : We have evaluated an intracardiac technique for the study of the electrophysiological patterns of early or subendocardial ischaemia in man. Simultaneous recordings of the paced endocardial evoked response and monophasic action potentials were obtained during pacing stress testing in 10 patients with reversible myocardial ischaemia. Early patterns of change occurred in both these recordings in response to regional ischaemia. Abnormal rate corrected shortening of the local repolarisation time in the paced endocardial evoked response from the left ventricular ischaemic zone diverging from control non-ischaemic values by a mean of 10.6% was paralleled by decreases in the simultaneous paced monophasic action potentials duration. A differential delay in the local activation time and conduction was also documented by the paced endocardial evoked response and monophasic action potential electrodes. Non-ischaemic control zones showed no changes in the pattern of activation and repolarisation. Disparate repolarisation times and asynchronous activation within the myocardium were thus consistently demonstrated during regional ischaemia. These changes in the endocardial paced evoked response and monophasic action potentials always preceded the appearance and regression of the clinical ischaemia. Intracavitary recordings may thus provide earlier and more sensitive detection of regional ischaemia during cardiac catheterisation or coronary artery surgery. The study of the patterns of activation and response could permit the assessment of interventions on the early electrical changes of ischaemia, and may bridge the gap between in vitro studies and the electrophysiological studies performed upon the intact heart.